How psychological beliefs affect the practices of recreational fishermen in singapore - Balachandran, Vivian (2017)
Managing recreational fishing and its impact on the environment is challenging as the regulations imposed by the relevant authorities in Singapore are undermined due to non- compliance. This study aims to (a) examine fishing practices of recreational anglers in Singapore by collecting behavioural observation data (N = 46) to investigate if fishing practices differ within and outside the legal areas and (b) utilising an online survey (N = 63) to assess how beliefs about the environmental impact of their fishing behaviour, environment attitudes, satisfaction with designated fishing areas and the perceived likelihood of enforcement impact anglers’ site preferences and fishing behaviour. Fisher’s Exact Test was carried out for the first part of the study and findings concluded that fishing practices within and outside designated fishing areas only differ in terms of the type of bait that is used (p = .01). Spearman’s Rank Correlation tests on the survey data revealed that beliefs had a negative correlation (rs = -.27, p = .02) with responsible fishing behaviour. Satisfaction with fishing sites is positively correlated with site preferences (rs = .49, p < .001), but negatively correlated with responsible fishing behaviour (rs = -.42, p < .001). Lastly, the perceived likelihood of enforcement was positively associated with responsible fishing behaviour (rs = .35, p = .003). Environmental attitudes generally did not appear to influence responsible fishing behaviour and site preferences. Implications of the findings and future research directions are discussed.